2016
DOI: 10.4178/epih.e2016041
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of factors related to active reproductive health behavior: a cross-sectional study Indonesian adolescent

Abstract: OBJECTIVESComplex and diverse factors are related to reproductive health (RH) behavior among adolescents according to the social and cultural context of each countries. This study examined the prevalence of active RH and factors related to active RH behavior among Indonesian adolescents.METHODSA cross-sectional study was conducted among 1,040 of students who were selected through a multi-stage random sampling technique. A self-administered questionnaire was developed, including the World Health Organization Il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 20 publications
4
42
0
5
Order By: Relevance
“…All of the instruments used in this study were previously validated and considered reliable from previous studies conducted by the authors. 1,8 After the implementation of the ARH short film screening that was friendly to local wisdom at the end of the program, an evaluation of the activities was done through the school community consultation. This activity was attended by students, teachers, and parents in assessing the students' progress in the ARH programs which had been implemented by the school for the past 4 months independently through focus group discussions (FGD).…”
Section: Program Supervision and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the instruments used in this study were previously validated and considered reliable from previous studies conducted by the authors. 1,8 After the implementation of the ARH short film screening that was friendly to local wisdom at the end of the program, an evaluation of the activities was done through the school community consultation. This activity was attended by students, teachers, and parents in assessing the students' progress in the ARH programs which had been implemented by the school for the past 4 months independently through focus group discussions (FGD).…”
Section: Program Supervision and Evaluationmentioning
confidence: 99%
“…Adolescence is a critical time for a person's growth and development when teenagers sometimes engage in risky sexual behavior, especially in terms of adolescent reproductive health (ARH). 1 During this period, adolescents may begin consuming pornography, engage in risky dating behavior, develop a sexual orientation disorder (LGBT), and become pregnant outside marriage. [2][3][4] Basic Health Research of Indonesia (Riskesdas) in 2010 found indications of pre-marital sexual behavior in 5% of adolescents aged 10-24 years.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study result that the preparation of reproductive health material for adolescents needs to add religious content. Health promotion programs for adolescents must be developed by taking into account prevalent social, cultural, religious values in preventing active reproductive health behaviors (Djannah, 2017;Susanto et al, 2016). Monitoring the growth of adolescents needs to be done continuously, especially in improving their spiritual intelligence to suppress reproductive health behavior that is risky for adolescents (Simak, Fitriyani, & Setiawan, 2019).…”
Section: Limited Field Testmentioning
confidence: 99%
“…The social aspect of HIV/AIDS patients happen to the social life such as stigmatisation and isolation may influence the psychological condition of the mother [ 12 ]. Health status is generally influenced by habit or culture adopted by the community because the act of treatment to be performed by the knowledge and perception of a person [ 13 ] [ 14 ]. Health status is a dynamic and individual circumstance that is influenced by personal and environmental factors.…”
Section: Introductionmentioning
confidence: 99%